The Modification Of Na-Montmorillonite By Salts Of Fatty Acids: An Easy İntercalation Process - Önder, Emel; Ersoy, Sabri; SARIER, NİHAL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
The organic modification of Na-montmorillonite (Na-MMT) clay by a reaction with the sodium salts of octadecanoic acid (SOD) and dodecanoic acid (SDD) was studied for the production of effectively intercalated and organophilic clays. The results of X-ray diffractometer (XRD) analysis reveal that the interlayer spacing of Na-MMT increased from 1.38 nm to 3.37-1.4-4 nm, 3.56-1.45 nm, 3.61-1.44 nm and 3.56-1.44 nm in the organoclays containing 393 mM SOD, 787 mM of SOD, 540 mM SDD and 1080 mM SOD, respectively. In the Fourier transform infrared spectrometer (FTIR) analyses, the stretching and bending vibrations of the hydroxyl groups of Na-MMT at 3619,3407 and 1634 cm(-1) 15 as well as the Si-O and Al-O vibrations of silica-alumina layers at 1039-534 cm(-1) 16 respond to the structural changes from hydrophilic to hydrophobic character. Thermogravimetric (TG) analyses results also suggest that the intercalation of SOD and SDD were achieved in the organoclays samples and the samples had permanent structural modifications, although they retained their inorganic character. The TEM-EDS and SEM results show that the SOD and SDD were well dispersed and intercalated throughout the interlayer spaces or adsorbed onto the clay surface. The suggested organic modification of Na-MMT is an easily applicable process in which the chemically stable, low cost and widely available SOD and SDD are used as intercalating agents. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Montmorillonite; Organoclays; XRD; FTIR; TEM-EDS; SEM; polymer/layered silicate nanocomposites; infrared-spectroscopy; adsorption; smectite; organoclays; complexes; clays; ftir; dispersions; exfoliation; Organokiller; Polimer / tabakalı silikat nanokompozitler; kızılötesi spektroskopi; emme; simektit; kompleksler; killer; dağılımlar; pul pul dökülme